APPROACH TO PROBLEM BASED LEARNING MODELS IN NURSING EDUCATION: SYSTEMATIC REVIEW - Primasari Rahmawati (UPT Penerbitan Universitas Jember, 2017)
Background: Profession nurse is one of the profession as a health worker who plays an important role in achieving health development goals. In producing competent nursing student graduates, educators need to design learning that can generate students' potential in using their critical thinking skills to solve problems. One of the learning approaches is to use the learning model of